Functional iridoid synthases from iridoid producing and non-producing Nepeta species (subfam. Nepetoidae, fam. Lamiaceae) - Aničić, Neda; Matekalo, Dragana; Skorić, Marijana; Gašić, Uroš; Nestorović Živković, Jasmina; Dmitrović, Slavica; Božunović, Jelena; Milutinović, Milica; Petrović, Luka; Dimitrijević, Milena; Anđelković, Boban; Mišić, Danijela (Frontiers in Plant Science, 2024)
Iridoids, a class of atypical monoterpenes, exhibit exceptional diversity within the Nepeta genus (subfam. Nepetoidae, fam. Lamiaceae).The majority of these plants produce iridoids of the unique stereochemistry, with nepetalactones (NLs) predominating; however, a few Nepeta species lack these compounds. By comparatively analyzing metabolomics, transcriptomics, gene co-expression, and phylogenetic data of the iridoid-producing N. rtanjensis Diklić & Milojević and iridoid-lacking N. nervosa Royle & Bentham, we presumed that one of the factors responsible for the absence of these compounds in N. nervosa is iridoid synthase (ISY). Two orthologues of ISY were mined from leaves transcriptome of N. rtanjensis (NrPRISE1 and NrPRISE2), while in N. nervosa only one (NnPRISE) was identified, and it was phylogenetically closer to the representatives of the Family 1 isoforms, designated as P5βRs. Organ-specific and MeJA-elicited profiling of iridoid content and co-expression analysis of IBG candidates, highlighted NrPRISE2 and NnPRISE as promising candidates for ISY orthologues, and their function was confirmed using in vitro assays with recombinant proteins, after heterologous expression of recombinant proteins in E. coli and their His-tag affinity purification. NrPRISE2 demonstrated ISY activity both in vitro and likely in planta, which was supported by the 3D modeling and molecular docking analysis, thus reclassification of NrPRISE2 to NrISY is accordingly recommended. NnPRISE also displays in vitro ISY-like activity, while its role under in vivo conditions was not here unambiguously confirmed. Most probably under in vivo conditions the NnPRISE lacks substrates to act upon, as a result of the loss of function of some of the upstream enzymes of the iridoid pathway. Our ongoing work is conducted towards re-establishing the biosynthesis of iridoids in N. nervosa.